Comparative Study of Rewards, Training and Ergonomics Parameters among Quality Award and Non-Quality Award Winning Manufacturing industries in Karnataka - Ravi Kumar R, Subrahmanya Bhat, Gururaj Upadyaya, Satyabodh M Raichur (Mathematical Statistician and Engineering Applications, 2023)
This work talks about comparative study of Employee involvement parameters such as top management and team building in quality award and non-quality award winning manufacturing organisation in Karnataka state in India. Parameters such as Rewards and Motivation, Training and skill development and Ergonomics and Work safety are examined with stastistically. The purpose is to identify differences in the manufacturing industries who have won quality awards such as Deming, CII-Exim and Ramakrishna Bajaj Awards etc. in terms of Rewards and Motivation, Training and skill development and Ergonomics and Work safety for Employee Involvement and to give suggestions to non-quality award winning organisation. For this survey has been extensively carried out to get response from employees across various manufacturing industries in Karnataka. Primary survey was carried out and received response from 736 out of which 650 ofnon quality award winning and 86 of quality award winning organisation from various industry in Karnataka a state in India.